Epac, Rap and Rab3 act in concert to mobilize calcium from sperm's acrosome during exocytosis - Ruete, María Celeste (2014)
BACKGROUND: Exocytosis of sperm's single secretory granule or acrosome (acrosome reaction, AR) is a highly regulated event essential for fertilization. The AR begins with an influx of calcium from the extracellular milieu and continues with the synthesis of cAMP and the activation of its target Epac. The cascade bifurcates into a Rab3-GTP-driven limb that assembles the fusion machinery and a Rap-GTP-driven limb that mobilizes internal calcium. RESULTS: To understand the crosstalk between the two signaling cascades, we applied known AR inhibitors in three experimental approaches: reversible, stage-specific blockers in a functional assay, a far-immunofluorescence protocol to detect active Rab3 and Rap, and single cell-confocal microscopy to visualize fluctuations in internal calcium stores. Our model system was human sperm with their plasma membrane permeabilized with streptolysin O and stimulated with external calcium. The inhibition caused by reagents that prevented the activation of Rap was reversed by mobilizing intracellular calcium pharmacologically, whereas that caused by AR inhibitors that impeded Rab3's binding to GTP was not. Both limbs of the exocytotic cascade joined at or near the stage catalyzed by Rab3 in a unidirectional, hierarchical connection in which the intra-acrosomal calcium mobilization arm was subordinated to the fusion protein arm; somewhere after Rab3, the pathways became independent. CONCLUSIONS: We delineated the sequence of events that connect an external calcium signal to internal calcium mobilization during exocytosis. We have taken advantage of the versatility of the sperm model to investigate how cAMP, calcium, and the proteinaceous fusion machinery coordinate to accomplish secretion. Because the requirement of calcium from two different sources is not unique to sperm and fusion proteins are highly conserved, our findings might contribute to elucidate mechanisms that operate in regulated exocytosis in other secretory cell types.